Perakitan Personal Komputer dan Instalasi Sistem Operasi (Windows) - Mikael Rivaldo; Muhammad Arifin; Diska Kurnia Azzahra Putra; Elkin Rilvani (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
Assembling a personal computer and installing the Windows operating system are important activities in mastering information technology. This research aims to provide an in-depth understanding of the computer assembly process and operating system installation. The methods used include a Research and Development (R&D) approach, hands-on practice, and question-and-answer sessions. The research results show that systematic assembly steps and proper installation can produce a well-functioning computer. In addition, initial testing after assembly is crucial to ensure that all devices are detected correctly. It is hoped that this research can serve as a reference for information technology education and enhance students' practical skills in the field of computers.